Paixões, acontecimentos e formas de vida em contos de Menalton Braff. Uma abordagem semiótica - Santos, Flávia Karla Ribeiro (2014)
In this paper, we analyze through the theoretical framework of French Semiotics, under Algirdas Julien Greimas, Jacques Fontanille and Claude Zilberberg's perspectives, the short stories “O gorro do andarillho” and “O zelador”, which are part of the book “A coleira no pescoço”, by Menalton Braff. In the first short story, a wanderer executed another wanderer in order to get his beanie back, object which keeps him warm at cold days. In the second text, a village janitor executed a dog, his partner and friend, punishing him for a robbery that would deprive him of a promotion. We examined the processes of doing, the passionate processes of fury and revenge of the protagonist subjects from both texts constituting the corpus of the research, as well as the ways of life which they have manifested, associated with happenings that they experience. Thus, we apply to the texts the elements of narrative semiotic, passion semiotic and tensive semiotic. Our aim is verifying how the tensivization of the manifested passions occurs and the way of the happenings erupt at the denouement of the stories, relating them to the ways of life of their actors. In this perspective, we associated the passionate scheme with tensive graphics, in order to demonstrate the gradation of tension from the passional subjects. We have noted that these subjects, when achieved the apex of patemic manifestation, they can assume new ways of life. We also analyzed the dialogue that the enunciator establishes with the elements from Freudian psychoanalytic discourse at the text “O Zelador”, considering the relevance from this interdiscourse in the constitution of the way of life from the protagonist actor at the denouement of the story. We have observed that the eruption of happenings, related to ways of life, is responsible for dehumanizing the protagonist actors. From this perspective, they are taken by passions of malevolence. Thus, we concluded that the manifestation of fury at both texts is caused by happenings which rupture the routine of the subject and take them to the revenge. This passion at the top of the recrudescence of the subjects' thymic load results in new happenings.